2013
DOI: 10.2214/ajr.12.9545
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Imaging Biomarkers of Stage I Cervical Cancer and Poor-Prognosis Histologic Features: Quantitative Histogram Analysis of Diffusion-Weighted MR Images

Abstract: Median ADC is lower in poorly compared with well or moderately differentiated tumors, while lower histogram-positive skew in adenocarcinoma compared with squamous cell carcinoma is likely to reflect the glandular content of adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
106
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 36 publications
4
106
1
1
Order By: Relevance
“…In body imaging, Kyriazi et al (34) showed an increase in ADCs and a later decrease in skewness and kurtosis in response to chemotherapy in patients GENITOURINARY IMAGING: Myometrial and Lymphovascular Invasion and Endometrial Tumor Grade Nougaret et al with metastatic ovarian and primary peritoneal cancer. More recently, ADC histographic analysis has been applied in patients with cervical cancer to the whole tumor volume instead of to selected ROIs to eliminate sampling bias (35). In this study, the authors showed lower mean ADCs in poorly differentiated tumors than those in well or moderately differentiated tumors (35).…”
Section: Author Contributionsmentioning
confidence: 67%
See 1 more Smart Citation
“…In body imaging, Kyriazi et al (34) showed an increase in ADCs and a later decrease in skewness and kurtosis in response to chemotherapy in patients GENITOURINARY IMAGING: Myometrial and Lymphovascular Invasion and Endometrial Tumor Grade Nougaret et al with metastatic ovarian and primary peritoneal cancer. More recently, ADC histographic analysis has been applied in patients with cervical cancer to the whole tumor volume instead of to selected ROIs to eliminate sampling bias (35). In this study, the authors showed lower mean ADCs in poorly differentiated tumors than those in well or moderately differentiated tumors (35).…”
Section: Author Contributionsmentioning
confidence: 67%
“…More recently, ADC histographic analysis has been applied in patients with cervical cancer to the whole tumor volume instead of to selected ROIs to eliminate sampling bias (35). In this study, the authors showed lower mean ADCs in poorly differentiated tumors than those in well or moderately differentiated tumors (35). The ability to predict high-grade endometrial cancer by using ADC histographic analysis of whole tumor volumes is of clinical interest for two reasons: First, histologic tumor grade is a strong predictor of nodal involvement (36); and second, there is relatively frequent discordance of the preoperative cytologic results with the findings at final surgical pathologic examination due to undersampling (37).…”
Section: Author Contributionsmentioning
confidence: 99%
“…The histogram approach has been increasingly used for heterogeneous tissues, allowing interpretation of the complex nature and features seen in tumors 17. Previous studies in adults have utilized histogram analysis of ADC and cerebral blood volume (CBV), which has been applied to a variety of scenarios including differentiation of true tumor progression from pseudoprogression,28, 29 response to chemotherapy,30 and grading of tumors 31, 32, 33. Most previous pediatric studies have reported mean or median ADC values based on a single section or slice, which does not address the heterogeneity seen in many abdominal tumors 7, 8…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been growing interest in the histogram analysis of ADC of the entire tumor volume, as this approach provides quantitative information on the distribution and frequency of ADCs and consequently on the heterogeneity of water molecules diffusivity within the whole tumor [14][15][16][17]. The histogram-based ADC analysis has shown capabilities in differentiating and grading brain tumors [14][15][16], and in the prediction of uterine cervical cancer recurrence [18,19].…”
mentioning
confidence: 99%